2009
DOI: 10.19206/ce-117174
|View full text |Cite
|
Sign up to set email alerts
|

The use of turbulization in preliminary fuel treatment in self-ignition engines

Abstract: It is possible to increase the effectiveness parameters of self-ignition engine performance as well as to decrease the emission of toxic compounds in exhaust gases by using preliminary catalytic fuel treatment - PROCESSING – executed directly in the injector body. In order to enhance the impact of the catalyst on the flowing fuel we propose to take advantage of the phenomenon of turbulization in injector passages. First results of tests on an engine of 359 type have shown an improvement of operating parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The most favorable results were obtained with a mixture of 80% diesel oil, 10% methanol, and 10% n-butanol. The use of a catalyst in the nozzle of fuel injectors in an engine with direct mechanical fuel injection was described in studies [11,12]. The research showed that the use of a catalytic reactor in the form of platinum on the non-working part of the needle reduced the emission of toxic substances to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The most favorable results were obtained with a mixture of 80% diesel oil, 10% methanol, and 10% n-butanol. The use of a catalyst in the nozzle of fuel injectors in an engine with direct mechanical fuel injection was described in studies [11,12]. The research showed that the use of a catalytic reactor in the form of platinum on the non-working part of the needle reduced the emission of toxic substances to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%